Identification and molecular characterisation of vascular-related defense genes against papaya dieback disease - Hamid, Muhammad Hanam (2017)
Malaysia is one of the world’s main exporters of papaya with an export value worth RM120 million per year. An outbreak of papaya dieback disease on 2003 lowered the market value up to 60% from the previous year, and remains affected since. Erwinia mallotivora, the causal bacteria for papaya dieback disease, enters the papaya plant either through natural openings or wounds, to penetrate into the petioles and stem, and subsequently colonizes the entire vascular system. This results in the appearance of water-soak lesion at the infected region and disruption of the plant’s upper meristem region, which produces papaya fruits. To date, the only solution to this problem is by demolishing all the infected papaya plants as it can easily be transmitted to other plants nearby. An alternative approach such as genetic engineering to avoid mass destruction of matured papaya plants is deemed critical. Hence, the aims of this study were to identify potential vascular-related defense genes using bioinformatics approach, isolate and characterize the genes from Eksotika papaya and subsequently to assess the functionality of the genes in transformed papaya seedlings challenged with E. mallotivora. This study has successfully identified vascular-related defense genes against papaya dieback disease using bioinformatics approach. After data mining of bioinformatics databases including The Arabidopsis Information Resources (TAIR), Arabidopsis thaliana Trans-factor and cis-element Prediction Database (ATTED), Phytozome, and National Center for Biotechnology Information (NCBI), identified five potential genes were then mapped onto the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway of Arabidopsis model plant. Orthologs of the Glycerol kinase (NHO1), Pathogenesis-related protein 1 (PR1b), Leucine-rich repeat receptor-like serine/threonine-protein kinase (EFR), RPM1 interacting protein 4 (RIN4) and Mitogen-activated protein kinase 4 (MPK4) genes were isolated and fully characterized from Carica papaya var. Eksotika I. NHO1 gene with an estimated size of 1572 base pair (bp) was hypothesized as defense-related gene against pathogen. The similar role was predicted with PR1b gene (492 bp), while EFR gene (741 bp) was postulated to be involved in pathogen signaling. In addition, RIN4 gene (540 bp) was suggested to be a member of resistance inducer upon pathogen invasion. MPK4 gene (1125 bp) was estimated to work in a cascade of mediating various responses against pathogens through different signaling pathway of defense responses. These genes were then sub cloned, in a sense orientation, into the pEAQ virus vector for subsequent transformation into papaya seedlings via Agrobacterium tumefaciens strain GV3101. The constructs were designated as pEAQ.NHO1, pEAQ.PR1, pEAQ.EFR, pEAQ.RIN4 and pEAQ.MPK4. Leaves of two months old papaya seedlings were infiltrated with A. tumefaciens strain GV3101 (OD600 = 1.5) harbouring each respective constructs. The transformed papaya seedlings were then challenged with E. mallotivora (cfu = 106) and exhibited disease symptoms development as early as day two after infection. Further profiling of the transgene expression in the papaya seedlings via real-time polymerase chain reaction (qRTPCR) analysis resulted in functional expression against the causal bacteria of this papaya dieback disease. Overexpression of PR1b and NHO1 genes resulted in high expression level in infected plants compared to the uninfected plants. While overexpression of MPK4 and RIN4 showed high fold changes compared to control plants, expression of MPK4 exhibited a repressed defense response via earlier development of symptoms in both infected and uninfected plants. In addition, overexpression of EFR showed a down-regulation expression for both infected and uninfected plants. These findings will lay the foundation for subsequent studies in developing a conceivable solution against this papaya dieback disease.